Promoting Impact by Creating Markets : Management and Measurement - Faye, Issa; Tran, Luyen (International Finance Corporation, Washington, DC, 2021)
This 100th EM Compass note explains why it is important to ‘create markets’ to promote development, and how development finance institutions and impact fund managers can draw on IFC’s Anticipated Impact Measurement and Monitoring system to assess the contribution of their investments to both market creation and project outcomes.